Food Fundamentals Leader's Guide - Joy C. Jordan; Linda D. Cook (EDIS)
Produced by the Florida 4-H Youth Programs and Department of Family, Youth and Community Sciences, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, February, 1999; reviewed, June 2002.